What is Called Doing Philosophy in the Philippines? - Rivera, Reynaldo Y. (Silliman Journal, 2023)
This essay claims that social science, and even natural scientific investigation in the Philippines, is a philosophical conduct that is fashioned in the spirit of logical positivism. As a philosophical conduct, social science writing is a "craft of the hand" that is rooted in thinking only if it "lets being be." Therefore, in the sense of Martin Heidegger's "letting be", empirical social science investigation is the individual's simplest thinking, but the hardest handwriting when achieved at its proper time. However, like pragmatism—which evaluates and resolves our intel-lectual activity in human experiences in the context of the Cartesian "I think"—logical positivism, which also views philosophy as a practical activity rather than as theory building in the Cartesian "I think," is concerned with the clarification of the meaning of statements for scientific investigation of the world. Hence, both schools proclaim that for a statement to be scientific and, thus, capable of being observed in order to solve problems in our human experience, it must pass the test of the verifiability through the process of what is known in social research as the operationalization of theories. The use of theories therefore in scientific research does not only permit us to abandon meditative thinking but also classifies social science research as a philosophical conduct in the fashion of inductive and deduc-tive reasoning that are fashioned in both pragmatic and logical positivistic science. This is the essence of "doing philosophy" in the Philippines. To concretize or situate the thinking and the doing of philosophy in the Philippines, Fr. Jaime Bulatao's "The Manilelio's Mainsprings" is analyzed. In the fashion of logical positivism, Fr. Bulatao established his verifiability criterion of mean-ings for "accurate" observation of the phenomenon being studied by translating the concept of "Filipino value" in practical terms, coming up with six observable criteria to establish the logical positivistic verifiability criterion of meanings. Using a modified Thematic Apperception Test (TAT), he collected about 900 stories from his 90 respondents. In order to prove his "self-evident first truth" about the Filipino value, in effect, Fr. Bulatao's findings of the so-called Filipino value is, in reality, his subjective estimation–a product of "force-fitting" of the reality of the Filipino value to his own criteria. This identified value is thus not a Filipino value, but his estimation of what constitutes the Filipino value, because he did not let the valueness of the Filipino value reveal itself from itself. Thus, doing philosophy in the Philippines is logical positivist it looks at philosophy as an activity in the context of human estimation through the operationally defined theories.